Cities & social change encounters with contemporary urbanism - Paddison, Ronan; McCann, Eugene (SAGE, 2014)
What is the city? What is the nature of living in the city? This text provides an in-depth understanding of the central issues associated with the city and how living in a city impacts its inhabitants. Theoretically informed and thematically rich, the book contains an eminent, international cast of contributors and contributions. It provides a critical analysis of the key thinkers, themes and paradigms dealing with the relationship between the built environment and urban life. It includes illustrative case studies, questions for discussion, further reading and web links. Examining the contradictions, conflicts and complexities of city living, this book is an essential resource for students looking to get to grip with the different theoretical and substantive approaches that make up the diverse and rich study of the city and urban life.